Severe acute respiratory syndrome-coronavirus-2 seroprevalence study in Pimpri-Chinchwad, Maharashtra, India coinciding with falling trend - Do the results suggest imminent herd immunity? - Amitav Banerjee; Bhargav Gaikwad; Atul Desale; Sudhir Laxman Jadhav; Hetal Rathod; Kajal Srivastava (Wolters Kluwer Medknow Publications, 2021)
Background: COVID-19 is a public health concern currently demanding continuous efforts to understand its epidemiology. Pimpri-Chinchwad township with a population of over 25 lakhs is located in Maharashtra, one of the worst affected states in India. After the incidence peaked in the township in mid-September 2020, cases started declining even as lockdown restrictions were eased. Objectives: A seroprevalence study was conducted to understand the transmission dynamics of the pandemic in this region. Methods: We carried out a population-based seroprevalence study for IgG antibodies for severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) among 5000 residents 12 years and above selected by the cluster random sampling. We selected 50 clusters in slums, 80 clusters in tenements, and 70 clusters from housing societies. The field work for collection of samples was carried out from October 07 to October 17, 2020. We used kit from Abbott (SARS-CoV-2 IgG), which employs chemiluminescent microparticle immunoassay technology. The prevalence of IgG antibodies was expressed as point estimates with 95% confidence intervals (CIs). These were weighted for areas and cluster effect and further adjusted for test performance. Results: The overall seropositivity for IgG was 34.04% (95% CIl 31.3%-36.8%). Slum dwellers had 40.9% positivity rate (95% CI 37.0%-44.7%), those in tenements 41.2% (95% CI 37.7%-44.8%) and people living in housing societies had 29.8% positivity (95% CI 25.8%-33.8%). Conclusion: A considerable proportion of population had encountered the novel coronavirus approaching partial, if not complete, herd immunity, which may partly explain the declining trend in spite of easing of lockdown restrictions.